DISORIENTASI PENDIDIKAN MADRASAH DI INDONESIA - Hasan Basri (POTENSIA: Jurnal Kependidikan Islam, 2017)
Madrasah in the Middle East has known eight or nine centuries before madrasah in Indonesia, which emerged as a reaction to the reform movement as well as a response to the policy of Dutch colonizers secular education. Madrasah got a decent place in Indonesia after rising SKB 3 minister (Minister of Interior, Minister of Education and Culture, and the Minister of Religious Affairs) in 1975, where madrasas equated with other schools in terms of the status of the diploma, graduates continuing education opportunities and changing schools. In a further development, the school as disoriented. It is caused by two things: first, a paradigm shift towards sekularistik. Education implementation has marred even be interpreted as a partial instead of a holistic paradigm as desired by Islam. Supposedly, the madrasa education as a whole should make Islam as a principle in the determination of educational objectives, the formulation of the curriculum and standard of value of science and the learning process, including determining the qualifications of teachers and school culture that will be developed in the madrasas. Second, the functional institutional weakness as a result of shifting the orientation and function of the family and their influence and societal demands materialistic-hedonistic.The weakness seen in a mess madrasa curriculum, not optimal role of teachers as well as school culture that is not in line with the will of Islam.